Panax quinquefolius polysaccharides ameliorate ulcerative colitis in mice induced by dextran sulfate sodium - Ren, Duo-duo; Chen, Ke-Cheng; Li, Shan-shan; Zhang, Yan-ting; Li, Zhi-man; Liu, Shuang; Sun, Yin-shi (Frontiers in Immunology, 2023)
This study aimed to investigate the ameliorative effect of the polysaccharides of Panax quinquefolius (WQP) on ulcerative colitis (UC) induced by dextran sulfate sodium (DSS) in mice and to explore its mechanism. Oral administration of WQP showed remarkable protective effects against colitis, presenting as a significantly lower DAI score of mice and an alleviated colon tissue injury. In the middle- and high-dose polysaccharides groups, the levels of pro-inflammatory cytokines IL-6, IL-8, IL-1β and TNF-α in the colonic tissue were significantly decreased (P < 0.05), while the levels of IL-4 and IL-10 were significantly increased (P < 0.05). The 16S rRNA gene sequencing results showed that WQP could regulate the composition and diversity of gut microbiota and improve its structure. The high-dose WQP group could significantly increase the contents of acetic acid, propionic acid, butyric acid, and total SCFAs. Different doses of WQP also increased the expression levels of tight junction proteins ZO-1, Occludin and Claudin-1. To sum up, WQP can regulate the gut microbiota structure of UC mice, accelerate the recovery of gut microbiota, and increase the content of SCFAs and the expression level of tight junction proteins in UC mice. This study can provide new ideas for the treatment and prevention of inflammatory bowel disease (IBD) and theoretical references for the application of WQP.